2019
DOI: 10.1111/hsc.12842
|View full text |Cite
|
Sign up to set email alerts
|

Senior manager decision‐making and interactions with frontline staff in intellectual disability organisations: A Delphi study

Abstract: Very little is known of the activities of the most senior managers in organisations providing social care in the community to people with intellectual disabilities. Yet the importance of the focus and activities of senior managers in directing and supporting staff practice and staff experiences is likely to be central to an organisation's functioning and support provided for staff and service users. This study employed Delphi methodology with a panel of 11 senior managers, mostly chief executives, managing sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…This study has value for researchers and practitioners, as the ecological perspective provides insight into recent studies on implementing and maintaining active support in various services, which have concluded that hands-on training and managerial leadership seem to be crucial organizational aspects (Beadle-Brown, Bigby, & Bould, 2015;Bigby & Beadle-Brown, 2018;Bigby, Bould, Iacono, Kavanagh, & Beadle-Brown, 2019;Deveau & McGill, 2016a, 2016b. As Bould, Beadle-Brown, Bigby, and Iacono (2016) (Deveau and McGill, 2019;Deveau, Gore, & McGill, 2020;Olivier-Pijpers, et al, 2018;Schippers, 2019;Tournier et al, 2020;Walker, 2012). During organizational changes, continuous discussions on aligning staff attitudes with the organizational vision, staff training in positive attitudes and reduced restraint use, and sufficient information about residents' needs to enhance resident-staff bonding are also necessary (Olivier-Pijpers, Cramm, & Nieboer, 2019;Philips & Rose, 2010;Walker, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This study has value for researchers and practitioners, as the ecological perspective provides insight into recent studies on implementing and maintaining active support in various services, which have concluded that hands-on training and managerial leadership seem to be crucial organizational aspects (Beadle-Brown, Bigby, & Bould, 2015;Bigby & Beadle-Brown, 2018;Bigby, Bould, Iacono, Kavanagh, & Beadle-Brown, 2019;Deveau & McGill, 2016a, 2016b. As Bould, Beadle-Brown, Bigby, and Iacono (2016) (Deveau and McGill, 2019;Deveau, Gore, & McGill, 2020;Olivier-Pijpers, et al, 2018;Schippers, 2019;Tournier et al, 2020;Walker, 2012). During organizational changes, continuous discussions on aligning staff attitudes with the organizational vision, staff training in positive attitudes and reduced restraint use, and sufficient information about residents' needs to enhance resident-staff bonding are also necessary (Olivier-Pijpers, Cramm, & Nieboer, 2019;Philips & Rose, 2010;Walker, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…As Bould, Beadle‐Brown, Bigby, and Iacono (2016) stated, implementing a new vision or support service is often supported by training and practice leadership, as well as performed through generally good management and proper working relationships. In practice, organizations’ long‐term commitment to change, translated into managers’ and psychologists’ practice leadership, with guidelines and information for staff and a focus on transparency in working relationships, is important for managing challenging behaviours (Deveau and McGill, 2019; Deveau, Gore, & McGill, 2020; Olivier‐Pijpers, et al, 2018; Schippers, 2019; Tournier et al, 2020; Walker, 2012). During organizational changes, continuous discussions on aligning staff attitudes with the organizational vision, staff training in positive attitudes and reduced restraint use, and sufficient information about residents’ needs to enhance resident–staff bonding are also necessary (Olivier‐Pijpers, Cramm, & Nieboer, 2019; Philips & Rose, 2010; Walker, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, by giving participants a personal experience of development through dialogic inquiry this intervention appears to have narrowed the gap between the school's philosophy and its practice.It influenced informal interactions and formal educational practices, thus creating a link between internal practices and outcomes that the school's external bodies use in commissioning specifications and inspection protocols. Creating coherence between informal practice and external expectations is an area of emerging research in leadership and culture change in the field of intellectual disability(Deveau et al, 2019). When we choose to see through a systemic lens, addressing challenging behaviour legitimises the consideration of interactions across the whole system, the rationale for which has been clearly demonstrated in the enduring legacy of Bronfenbrenner's seminal work(1979).…”
mentioning
confidence: 99%